Nurse Work Stress in Inpatient Room of Pasar Minggu Regional General Hospital, South Jakarta - Siregar, Tatiana -; Kurniarti, Tri -; Widakdo, Giri - (Jurusan Keperawatan FIKES UNSOED, 2020)
A nurse is a professional medical personnel at the forefront of hospital services. The number of nurses is the highest and they continuously work on shifts for up to 24 hours. For the past two years, Pasar Minggu Regional General Hospital, South Jakarta has had an increasing number of patients along with the regulation of Social Security Organizing Agency (BPJS), which every hospital has to apply, this condition burdens the nurses and causes work stress. This research aims to investigate the experiences of the nurses regarding work stress in the inpatient rooms of the General Hospital Region, South Jakarta. The research method is qualitative phenomenology, with 10 nurse participants taken using purposive sampling. The researchers carried out the retrieval of data by means of structured and in-depth interviews, observations and notes. The analysis data utilized the Colaizzi method, which resulted in four main themes, i.e., understanding the state of work stress, the response of work stress, coping mechanisms and the expected support from the hospital leaders. The hospital leaders are expected to be able to make policies in managing nurse work design, which is in accordance with the competencies, so that the nurses do not experience work stress and will eventually benefit the hospital and patients.